2013
DOI: 10.1089/ten.tea.2011.0372
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tissue Specificity on the Performance of Extracellular Matrix in Improving Endothelialization of Cardiovascular Implants

Abstract: Natural extracellular matrix (ECM) deposited in situ by cultured endothelial cells (ECs) has been proven effective in accelerating endothelialization of titanium (Ti) cardiovascular implants (CVIs) in our previous studies. In this study, the ECM deposited by smooth muscle cells (SMCs) was used in comparison to investigate the effects of tissue specificity of the ECM on the ability to accelerate endothelialization of CVIs. The results demonstrated that the ECM deposited by ECs and SMCs (EC-ECM, SMC-ECM, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Functional and structural components within the ECM contribute to the extracellular environment specific to each tissue and organ [24]. The complexity of the ECM has proven difficult to recapitulate in its entirety, with attempts often limited to mimicking only ECM structure using synthetic biomaterials [5] or mimicking composition by adding purified ECM components [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional and structural components within the ECM contribute to the extracellular environment specific to each tissue and organ [24]. The complexity of the ECM has proven difficult to recapitulate in its entirety, with attempts often limited to mimicking only ECM structure using synthetic biomaterials [5] or mimicking composition by adding purified ECM components [6].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, complex tissues such as heart and lung have been decellularized to obtain native-ECM scaffolds without particular regard for any specific region of the organ or preservation of potential stem cell niches [16, 17]. Previous studies have shown that cells native to a particular region of the organ (e.g., vascular endothelium, liver sinusoidal cells) display ECM recognition and specificity [24]. If this site-specific recognition could be extended to stem cells, the choice of matrix would become an important consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Under physiological blood shear stress conditions, a larger number of cells remained adhered to ECM than to a conventional coating such as collagen with the higher expression of both integrins α2 and β1 . ECs ECM and SMCs ECM prepared by decellularizing the cultured ECs and SMCs were also proved to improve the surface's blood compatibility and pro‐endothelialization ability, while there is a little difference between the ECs ECM and SMCs ECM on surface re‐endothelialization: SMCs ECM contributed to more ECs adhesion and proliferation on its surface compared ECs ECM, while ECs ECM promoted the adherent ECs release more NO and PGI 2 . Learning from this data, ECM secreted by SMCs and ECs played different roles in the vascular endothelial growth microenvironment, and further speculation can be performed that healthy SMCs is a sine qua non factor for the ECs physiological growth.…”
Section: What Natural Factors Influence the Structure And Function Ofmentioning
confidence: 99%
“…ECM immobilization is a common and valid assay for surface modification of cardiovascular implants. The whole ECM components secreted by the ECs show better biocompatibility compared with single protein . Nevertheless, the in vitro cultured ECs with cobblestone appearances show deficiency on their ECM secretion compared to in vivo natural ECs with spindle appearances, and the later maintain their exposure to the physiological BFSS, which influence is able to simulate by the surface micro‐pattern with appropriate scales .…”
Section: In Situ Constructing Vascular Endothelial Growth Microenviromentioning
confidence: 99%
“…He et al found the use of nanofi ber blends to mimic extracellular material to be successful in providing a scaffold for attachment and proliferation of viable human coronary artery endothelial cells (He et al 2005 ). In a hybrid approach to this method, Tu et al found that seeding a matrix with smooth muscle cells additionally aided in the formation of a confl uent endothelial layer (Tu et al 2013 ). L'Heureux et al showed that it is possible to develop a tissue-engineered vascular graft in vivo entirely from the host's own cells with mechanical and antithrombogenic capacity for up to a functional lifetime of 8 months (L'Heureux et al 2006 ).…”
Section: Stents and Vascular Graftsmentioning
confidence: 99%